Azithromycin Promotes the Osteogenic Differentiation of Human Periodontal Ligament Stem Cells after Stimulation with TNF-α - Tingting Meng; Ying Zhou; Jingkun Li; Meilin Hu; Xiaomeng Li; Pingting Wang; Zhi Jia; Liyu Li; Dayong Liu (Stem Cells International)
Background and Objective. This study investigated the effects and underlying mechanisms of azithromycin (AZM) treatment on the osteogenic differentiation of human periodontal ligament stem cells (PDLSCs) after their stimulation with TNF-α in vitro. Methods. PDLSCs were isolated from periodontal ligaments from extracted teeth, and MTS assay was used to evaluate whether AZM and TNF-α had toxic effects on PDLSCs viability and proliferation. After stimulating PDLSCs with TNF-α and AZM, we analyzed alkaline phosphatase staining, alkaline phosphatase activity, and alizarin red staining to detect osteogenic differentiation. Real-time quantitative polymerase chain reaction (RT-qPCR) analysis was performed to detect the mRNA expression of osteogenic-related genes, including RUNX2, OCN, and BSP. Western blotting was used to measure the NF-κB signaling pathway proteins p65, phosphorylated p65, IκB-α, phosphorylated IκB-α, and β-catenin as well as the apoptosis-related proteins caspase-8 and caspase-3. Annexin V assay was used to detect PDLSCs apoptosis. Results. TNF-α stimulation of PDLSCs decreased alkaline phosphatase and alizarin red staining, alkaline phosphatase activity, and mRNA expression of RUNX2, OCN, and BSP in osteogenic-conditioned medium. AZM enhanced the osteogenic differentiation of PDLSCs that were stimulated with TNF-α. Western blot analysis showed that β-catenin, phosphorated p65, and phosphorylated IκB-α protein expression decreased in PDLSCs treated with AZM. In addition, pretreatment of PDLSCs with AZM (10 μg/ml, 20 μg/ml) prevented TNF-α-induced apoptosis by decreasing caspase-8 and caspase-3 expression. Conclusions. Our results showed that AZM promotes PDLSCs osteogenic differentiation in an inflammatory microenvironment by inhibiting the WNT and NF-κB signaling pathways and by suppressing TNF-α-induced apoptosis. This suggests that AZM has potential as a clinical therapeutic for periodontitis.